Stability Analysis of Additive Runge-Kutta Methods for Delay-Integro-Differential Equations - Hongyu Qin; Zhiyong Wang; Fumin Zhu; Jinming Wen (International Journal of Differential Equations)
This paper is concerned with stability analysis of additive Runge-Kutta methods for delay-integro-differential equations. We show that if the additive Runge-Kutta methods are algebraically stable, the perturbations of the numerical solutions are controlled by the initial perturbations from the system and the methods.